Dakwah di Cybers Space: Peluang dan Tantangannya - Armaidi Tanjung (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
The development of information technology (IT) turned out to have changed the order of human life so quickly. Without realizing it, IT changes the behavior, attitudes, views, patterns and ways of dealing with this life by every human being. The unlimited reach of cyber space, besides being beneficial to human life, also brings disaster. The influence of cyber space on the implementation of Islamic da'wah is also unavoidable. If cyber space is used for da'wah activities, many things can be developed. Cyber space with various advantages, it is possible to make da'wah activities more meaningful, easy, inexpensive, and read by many people without limits. The dai, religious leaders, clerics, kiai, Muslim scholars, it is fitting to use cyber space as a medium of alternative da'wah, in addition to da'wah on the pulpit and on television.